RIFM FRAGRANCE INGREDIENT SAFETY ASSESSMENT, 2, 2, 4-trimethyl-4-phenyl-butane-nitrile CAS Registry Number 75490-39-0. (December 2017) - Api, A.M.; Belsito, D.; Botelho, D.; Browne, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Fryer, A.D.; et al.
Highlights: 2, 2, 4-Trimethyl-4-phenyl-butane-nitrile safety assessment based on RIFM's criteria. Safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data and/or TTC.